PEMANFAATAN KOPERASI SEKOLAH SEBAGAI SUMBER BELAJAR IPS DI SMPN 2 AIKMEL LOMBOK TIMUR - Yuliani, Meri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2020)
This research is motivated by the lack of use of ips learning resources that are relevant to the lives of students both in the community and school environment where students gain knowledge. The purpose of this research is to find out; (1) the conditions of social studies learning (2) the use of cooperatives as a source of social studies learning. This study uses a qualitative research approach. This type of research used in this research is descriptive qualitative. descriptive. The data collection instruments were observation, interview and documentation. Based on the results of research at SMPN 2 Aikmel, the role of the existence of student cooperatives as social studies learning laboratories, namely to help students meet the needs of students at school, foster values ​​of honesty and a sense of responsibility, increase student knowledge, especially economic lessons, educate students in organization. Meanwhile, the student cooperative of SMPN 2 Aikmel has a role, namely to help meet all the needs of students in the school, as a place to sell student goods.